Indonesian Peasants in the Constellation of Power and the Trajectory of Capitalism - Ekayanta, Fredick Broven (Journal of Peasants’ Rights, 2023)
As an agricultural nation, Indonesia has a paradoxical situation where its peasants have never been a dominant political force. This condition can be seen from the lack of regulations in favor of peasants, the rampant criminalization of peasants in land conflicts, to the absence of peasant-based movements and political parties. This article explains the position of peasants in the constellation of power and the trajectory of capitalism in Indonesia. The article concludes that peasants have always been in a marginal political position at various periods, starting from the feudal era to the era of capitalism introduced by the Dutch colonial government. This position continued in the era of independent Indonesia where peasants remained on the periphery of Indonesian politics which was dominated by the bureaucracy and military during the New Order and oligarchy during the Reformation era.